Educação a distância: sua viabilidade para capacitação de professores de geografia - Maria Beatriz Junqueira Bernardes (Sociedade & Natureza)
In the beginning of the 21st century has been delineated great changes in the teaching-learningprocedures in partnership with dissemination process of information and the use of new technolo-gies. The distanced education allows improving the quality of the current teaching and conduct tothe distant population of teaching institutions all the current teaching conquers. Due to the needof a permanent training in all the segments of the society, the education could not be forgotten. Theway for a permanent training is the distanced education through Internet, because it makes itpossible for the students to choose the best time to study. Through the accomplished research, inUberlândia it was possible to identify that the educators that work with Fundamental Teaching(Intermediate and Advanced Cycle) they are interested in the distanced training course throughInternet.